The influence of plant natural fibers on swelling behavior of polymer hydrogels - Laftah, Waham Ashaier (SAGE Publications, 2014)
Central composite design method was used to design and optimize the best content of initiator, cross-linker, neutralizer and plant natural fibers of cotton and oil empty fruit bunch. The effect of buffer and saline solution on plant natural fiber based polymer hydrogel composites was investigated. The influences of plant natural fiber content and swelling behavior of polymer hydrogels were studied. Natural fibers had positive effect on polymer hydrogels in terms of absorption capacity and swelling rate. Polymer hydrogel composite of natural fiber with higher cellulose content had better swelling properties than that of less cellulose content and plain hydrogels. Polymer hydrogel composite base of high cellulose fiber content is less affected by the pH and ion concentration of the external solutions.